Molecular Regulators of Muscle Mass and Mitochondrial Remodeling Are Not Influenced by Testosterone Administration in Young Women - Horwath, Oscar; Moberg, Marcus; Hirschberg, Angelica Lindén; Ekblom, Björn; Apró, William (Frontiers in Endocrinology, 2022)
Testosterone (T) administration has previously been shown to improve muscle size and oxidative capacity. However, the molecular mechanisms underlying these adaptations in human skeletal muscle remain to be determined. Here, we examined the effect of moderate-dose T administration on molecular regulators of muscle protein turnover and mitochondrial remodeling in muscle samples collected from young women. Forty-eight healthy, physically active, young women (28 ± 4 years) were assigned in a random double-blind fashion to receive either T (10 mg/day) or placebo for 10-weeks. Muscle biopsies collected before and after the intervention period were divided into sub-cellular fractions and total protein levels of molecular regulators of muscle protein turnover and mitochondrial remodeling were analyzed using Western blotting. T administration had no effect on androgen receptor or 5α-reductase levels, nor on proteins involved in the mTORC1-signaling pathway (mTOR, S6K1, eEF2 and RPS6). Neither did it affect the abundance of proteins associated with proteasomal protein degradation (MAFbx, MuRF-1 and UBR5) and autophagy-lysosomal degradation (AMPK, ULK1 and p62). T administration also had no effect on proteins in the mitochondria enriched fraction regulating mitophagy (Beclin, BNIP3, LC3B-I, LC3B-II and LC3B-II/I ratio) and morphology (Mitofilin), and it did not alter the expression of mitochondrial fission- (FIS1 and DRP1) or fusion factors (OPA1 and MFN2). In summary, these data indicate that improvements in muscle size and oxidative capacity in young women in response to moderate-dose T administration cannot be explained by alterations in total expression of molecular factors known to regulate muscle protein turnover or mitochondrial remodeling.